2020
DOI: 10.4414/smw.2020.20222
|View full text |Cite
|
Sign up to set email alerts
|

The cellular prion protein beyond prion diseases

Abstract: The cellular prion protein (PrP C ), a cell surface glycoprotein originally identified for its central role in prion diseases (also called transmissible spongiform encephalopathies), has recently been implicated in the pathogenesis of other neurodegenerative disorders, such as Alzheimer's and Parkinson's diseases, by acting as a toxicity-transducing receptor for different misfolded protein isoforms, or in some case by exerting neuroprotective effects. Interestingly, PrP C has also been reported to play unexpec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 150 publications
(193 reference statements)
0
17
0
Order By: Relevance
“…Secondly, a more general role for PrP C in immunological quiescence has been proposed, based on its pattern of expression in immune privilege organs as well as its cytoprotective and immune-regulatory function [ 108 ]. Mechanistically, PrP C may, by itself, induce cell signalling events sustaining immunomodulation, and thereby temper inflammation [ 8 , 108 ]. On the other hand, tumour associated PrP C controls the levels of several effectors known to promote immune evasion.…”
Section: Evading Immune Destruction (Emerging Hallmark)mentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, a more general role for PrP C in immunological quiescence has been proposed, based on its pattern of expression in immune privilege organs as well as its cytoprotective and immune-regulatory function [ 108 ]. Mechanistically, PrP C may, by itself, induce cell signalling events sustaining immunomodulation, and thereby temper inflammation [ 8 , 108 ]. On the other hand, tumour associated PrP C controls the levels of several effectors known to promote immune evasion.…”
Section: Evading Immune Destruction (Emerging Hallmark)mentioning
confidence: 99%
“…The variety of PrP C isoforms may explain why PrP C has been ascribed a plethora of functions, ranging from broad roles in the physiology of the central nervous system, resistance to various types of stresses, cell fate and differentiation, cell adhesion and cell signalling [ 6 ]. Unravelling the physiological roles exerted by PrP C has long emerged as a powerful strategy to understand how the corruption of these functions may contribute to pathological contexts, not only prion diseases [ 7 ] but also other disorders, including Alzheimer’s disease, immune disorders or cancer [ 8 ]. Obviously, the research dedicated to prion and cancer has lagged behind that of neurodegeneration, but this field is now becoming the focus of growing interest.…”
Section: Introductionmentioning
confidence: 99%
“…Although not examined to our knowledge in the context of CRC, the mechanotransduction-dependent activation of YAP/TAZ was found to play an important role in intestinal repair after tissue damage [80]. In the context of CMS4 CRC, we recently established that YAP/TAZ are under the control of the cellular prion protein, denoted PrP C , a protein mainly known for its involvement in neurodegenerative disease [81] and whose role in cancer progression is attracting interest [82,83] (see Figure 6). More precisely, we uncovered that expression of the PrP C -encoding gene PRNP, which is enriched in CMS4 tumours, is associated with a YAP/TAZ signature in CRC patients and cell lines [70].…”
Section: Upstream Pathwaysmentioning
confidence: 99%
“…In this respect, it is worth noting that CMS4 tumours display downregulation of all DNA repair pathways, which is proposed to result from hypoxia-induced oxidative stress [86]. Thus, whether the interplay between PrP C and YAP/TAZ in CMS4 CRC also In the context of CMS4 CRC, we recently established that YAP/TAZ are under the control of the cellular prion protein, denoted PrP C , a protein mainly known for its involvement in neurodegenerative disease [81] and whose role in cancer progression is attracting interest [82,83] (see Figure 6). More precisely, we uncovered that expression of the PrP C -encoding gene PRNP, which is enriched in CMS4 tumours, is associated with a YAP/TAZ signature in CRC patients and cell lines [70].…”
Section: Upstream Pathwaysmentioning
confidence: 99%
“…Human cytoplasmic prion protein (PrP) is a glycosylphosphatidylinositol (GPI) anchored membrane‐bound glycoprotein, which is highly conserved in mammals such as in normal human tissues and cells, and most abundantly expressed in the nervous system (Manni et al., 2020 ). Recent studies reported that PrP is involved in the inhibition of hippocampal synaptic plasticity and LTP of Aβ oligomers as a high‐affinity specific binding site for Aβ oligomers (Larson et al., 2012 ; Um et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%